Antibacterial activity of hemocyanin from red swamp crayfish (Procambarus clarkii). Issue 75 (April 2018) - Qin, Zhendong; Babu, V. Sarath; Wan, Quanyuan; Muhammad, Asim; Li, Jun; Lan, Jiangfeng; Lin, Li
Abstract: Hemocyanins (HMC): the copper-containing respiratory proteins present in invertebrate hemolymph, which plays many essential roles in the immune system. Currently, little is known about the HMC domains of Procambarus clarkii ( P. clarkii ) and their function in antimicrobial immune response. In this present study, we comparatively studied the expression pattern of native Pc HMC with the three recombinant proteins of variable domains of crayfish hemocyanin ( Pc HMC-N, N-terminal domain of hemocyanin; Pc HMC-T, tyrosinase domain of hemocyanin; Pc HMC-C, C-terminal domain of hemocyanin). The results showed that three purified recombinant proteins had a strong binding to various bacteria and lipopolysaccharides that further highly agglutinated. The HMCs recombinant proteins showed strong antibacterial activity against V. parahaemolyticus and S. aureus by bacterial growth inhibition, phenoloxidase (PO) and phagocytosis assays. Specifically, r Pc HMC1-T and r Pc HMC1-C inhibited both the bacteria efficiently, r Pc HMC1-T was highly upregulated the PO activity than the other recombinant proteins. Whereas, recombinant proteins pretreated crayfish hemocytes participated in phagocytosis activity, r Pc HMC1-N and r Pc HMC1-C proteins had a profound effect than the r Pc HMC1-T on S. aureus and V. parahaemolyticus phagocytosis. The crayfish hemocyanin domains clearly exhibited antibacterial and phagocytic activities against both the bacteria, suggesting that its variable domains of hemocyanin have the different function on specific pathogen during the assault of pathogens. Highlights: PcHMC1 was up-regulated in hepatopancreas post of bacterial challenge. All the domains of PcHMC1 showed similar binding activity against bacteria and polysaccharides. Different domains of hemocyanin have its own specific antibacterial activity.